The epidemiological status of malaria during 2006 to 2018 in Larestan city, Southern Iran: A cross-sectional study - Mohammad-Rafi Bazrafshan; Mohammad Reza Foroutani; Ahmadreza Eidi; Hamed Delam (Shiraz University of Medical Sciences, 2020)
Abstract Background: Malaria has been considered by health systems as one of the most dangerous human infectious diseases. In Iran, the disease has caused great economic and social damage to the country. The present study was designed to identify the epidemiological situation of malaria during 2006 to 2018 in the southern region of Fars province, southern Iran. Methods: This is a cross-sectional study. The study population consisted of all people with malaria whose information was recorded at the Larestan Infectious Diseases Center from 2006 to 2018. To extract the data, a checklist was used that included information such as the total number of smears performed each year, the number of positive smears, age of the individual, sex, type of malaria species, and the month of the disease. Results: Out of a total of 85,201 smear tests performed to identify malaria in the region, 190 had positive smear tests. The majority of the positive cases were Afghan nationalities. Most cases of the disease were seen in 2017, 2008 and 2016, respectively. In all years, men were more likely than women to have malaria, and the highest prevalence was in the age group of 21-30  and 11-20 years, respectively. Conclusion: Despite the relative decrease in malaria cases in recent decades in Larestan city,  in recent years, especially from 2014 to 2018, the increasing trend of the disease has been relatively shown again, so making active diagnosis, equipping health systems and doing more blood smears tests are necessary to reduce the prevalence of malaria in this region.